Sustainable Development of Competitiveness of Meat Cattle Breeding - OMARKHANOVA, Zhibek; AMANGELDIJEVA, Zhanar; ABYLKASSIMOVA, Zhibek; KHASSENOVA, Klara; RAMASHOVA, Aissulu; KOITANOVA, Aliya (Journal of Environmental Management and Tourism, 2018)
The article considers the problems of ensuring the sustainable development of competitiveness of the meat industry in the Republic of Kazakhstan. Along with this an analysis was made of the current conditions for the formation of meat cattle breeding during the periods from 1990 and 2008 to 2015 as well as the dynamics of the number of cattle, meat production and meat consumption per capita. The main reasons are given for the insufficient development of the meat industry in comparison with the world's meat exporters. Information is provided on the implementation of planned indicators for the purchase of cattle in the period from 2011 to 2015 it is justified that state assistance in creating a competitive agro-industrial complex will ensure food security as well as increase the employment of the rural population.